Pemanfaatan Media Sosial Sebagai Media Promosi dalam Pemasaran Produk pada Koperasi Tahu dan Tempe - Diana Novita; Agus Herwanto; Meiyanti Nurchaerani (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Marketing is a social and managerial process that makes individuals / groups get what they need and want by creating, offering and exchanging valuable products to other parties. Marketing involves many different activities that add value to the product when the product moves through the system. The current marketing system that is becoming a new trend is the online marketing system. With the emergence of a new era in the field of marketing which is referred to as the digital marfketing era, we entrepreneurs must consider various online media to be used in determining the company's strategic planning. One of the media intended is social media. Social media that is widely used by everyone and is quite popular in Indonesia today is Facebook and Instagram. Indonesia is one country with a high number of Facebook users, certainly has a great opportunity and opportunity to use social media as part of strategic marketing planning. Marketing through online media has many great advantages, one of which is that the costs incurred are relatively cheaper compared to other media in carrying out product promotion activities. In this paper, we discuss the promotion process for tofu and tempeh entrepreneurs in Indonesia. As we know, tofu and tempeh are one of the foods that can be categorized as a companion to the staple food of the Indonesian people. This soy-based food is very popular with all levels of society in Indonesia. However, tempeh and tofu are still categorized as food for the lower class. Meanwhile, we still import raw materials to get tofu and tempeh from abroad. The irony is that sounds, but, that's what happens now. The lack of knowledge of the tofu and tempeh artisans is what makes this commodity not glimpsed by circles other than the middle and lower classes. Therefore, we must educate the artisans of tofu and tempeh and teach them to know the tofu and tempeh globally. Increased knowledge and utilization of social media, one way to help boost the marketing of tofu and tempeh